The United States–China Competition in the Asia-Pacific Region: From Economic Cooperation to Geopolitical conflict (Journal of Imam Al-Kadhim College, 2026)
This study examines the U.S.–China competition in the Asia-Pacific region as one of the most prominent manifestations of transformation in the contemporary international system. It focuses on the shift of this competition from economic cooperation to geopolitical rivalry, analyzing its economic, military, and technological dimensions. The research also highlights the implications of this competition for regional security, particularly the naval arms race, as well as the positions of East and Southeast Asian countries. The study concludes that the continuation of this rivalry without effective regulatory frameworks may lead to further regional instability, posing risks to international peace and security.
Keywords: U.S.–China Competition; Asia-Pacific; Regional Security; Naval Arms Race; Geopolitics